2014
DOI: 10.1377/hlthaff.2014.0127
|View full text |Cite
|
Sign up to set email alerts
|

PEDSnet: How A Prototype Pediatric Learning Health System Is Being Expanded Into A National Network

Abstract: Except for a few conditions, pediatric disorders are rare diseases. Because of this, no single institution has enough patients to generate adequate sample sizes to produce generalizable knowledge. Aggregating electronic clinical data from millions of children across many pediatric institutions holds the promise of producing sufficiently large data sets to accelerate knowledge discovery. However, without deliberately embedding these data in a pediatric learning health system (defined as a health care organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
138
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 139 publications
(139 citation statements)
references
References 22 publications
1
138
0
Order By: Relevance
“…Thus, though the registry had initially focused on measuring simple remission rates, partnering with patients revealed that patients and their families were more interested in prolonged, steroid-free remissions, which have improved from 55% to 78% in participating practices. 16 The network has now added two UK sites (in Cambridge and London).…”
Section: Unmet Potentialmentioning
confidence: 99%
“…Thus, though the registry had initially focused on measuring simple remission rates, partnering with patients revealed that patients and their families were more interested in prolonged, steroid-free remissions, which have improved from 55% to 78% in participating practices. 16 The network has now added two UK sites (in Cambridge and London).…”
Section: Unmet Potentialmentioning
confidence: 99%
“…These data create unique opportunities to advance population health through research (eg, comparative-effectiveness studies), quality improvement (eg, measurement of physician performance), and public health activities (eg, disease surveillance). [2][3][4] Enthusiasm for the concept of rapid learning health systems is substantial within the oncology community, driven by the desire to optimize clinical practice and advance research in a field with a particularly complex evidence base and heterogeneous disease. 5 The American Society of Clinical Oncology aims to launch CancerLinQ, 6 which will collect data from a wide range of sources, including patient records, to support clinical cancer care and conduct cancer research.…”
Section: Introductionmentioning
confidence: 99%
“…There is also a robust, asynchronous communication infrastructure featuring a newsletter, blog and social media platforms on Twitter, Facebook and Instagram. [20] All ICN members are encouraged to continuously design and test network-wide, center-specific, and personal innovations to make collaborative and participatory care more efficient and effective, ultimately leading to improved outcomes. They also use communication structures to share the status of innovations with the network and learn from and apply the work from other centers to their own.…”
Section: Settingmentioning
confidence: 99%